Performance and mechanism of ether-based binder (KH-PE) in electrochemically switched ion exchange lithium extraction from salt lake brine with high Mg/Li ratio - Tianyu Feng; Qian Xu; Beichen Sun; Yulong Zhang; Can Wang; Xiao Du; Yongguo Li; Fengfeng Gao; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2026)

Substrate source and mineral protection synergistically govern the temperature response of lake sediment organic carbon - Beichen Wang; Xiaoxi Sun; Zhen Yang; Xinyi Li; Min Cai; Bingfu Yao; Li Liu; Tianran Sun; Jian Yang; Jibin Han; Xiying Zhang; Jianping Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

5-HMF-driven microporous N, O-dual doped carbon materials based on chitosan for syngas purification and CO2 capture - Jinpeng Zhai; Chao Liu; Lijuan Sun; Beichen Xue; Yongxin Wu; Rui Xiao (Carbohydrate Polymers, 2026)

Antagonistic effect of changing salinity and dissolved organic carbon on N2O production via different pathways in saline lakes - Xiaoxi Sun; Beichen Wang; Jian Yang; Hui Yu; Bingfu Yao; Mingxian Han; Shenyan Dai; Teng Wen; Jibin Han; Xiying Zhang; Jinbo Zhang; Hongchen Jiang (Water Research, 2025)

LLTO-based electrodes for selective lithium extraction from high Mg2+/Li+ brines: Performance and mechanistic insights - Ran Zhang; Jialu Chen; Qian Xu; Beichen Sun; Xiao Du; Shanxia Luo; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2025)

Substrate chemistry trumps mineral protection in governing temperature sensitivity of organic carbon mineralization in saline lake sediments - Beichen Wang; Xiaoxi Sun; Zhen Yang; Xinyi Li; Bingfu Yao; Min Cai; Tianran Sun; Jian Yang; Jibin Han; Xiying Zhang; Hongchen Jiang (Geochimica et Cosmochimica Acta, 2025)

Dual impacts of human activities on land cover and carbon storage in the Yellow River Delta (1986–2023) - Boyang Sun; Houjie Wang; Xiao Wu; Naishuang Bi; Guoyang Wang; Mengyan Wang; Beichen Wang (Ocean & Coastal Management, 2025)

Temperature response of magnetic susceptibility and pore structure of white Bleached sandstone - Beichen Du; Jishi Geng; Qiang Sun; Xin Hu; Hao Huang; Pengda Ma; Pengfei Li (Journal of Applied Geophysics, 2025)

Salinity change induces distinct climate feedbacks of nitrogen removal in saline lakes - Xiaoxi Sun; Ehui Tan; Beichen Wang; Zixuan Gan; Jian Yang; Jibin Han; Xiying Zhang; Shuh-ji Kao; Gary King; Hailiang Dong; Hongchen Jiang (Water Research, 2023)

Distinct Assembly Mechanisms for Prokaryotic and Microeukaryotic Communities in the Water of Qinghai Lake - Mingxian Han; Jianrong Huang; Jian Yang; Beichen Wang; Xiaoxi Sun; Hongchen Jiang (Journal of Earth Science, 2023)

Microbial carbon fixation and its influencing factors in saline lake water - Jianrong Huang; Jian Yang; Mingxian Han; Beichen Wang; Xiaoxi Sun; Hongchen Jiang (Science of The Total Environment, 2023)

LncRNA RAD51-AS1 Regulates Human Bone Marrow Mesenchymal Stem Cells via Interaction with YBX1 to Ameliorate Osteoporosis - Beichen Li; Jing Wang; Fangrong Xu; Qinjue Wang; Quan Liu; Guantong Wang; Dengshun Miao; Qiang Sun (Stem Cell Reviews and Reports, 2023)

Transcriptomic and Metabolomic Analyses Provide Insights into the Growth and Development Advantages of Triploid Apostichopus japonicus - Jiahui Xie; Yi Sun; Yue Cao; Lingshu Han; Yuanxin Li; Beichen Ding; Chuang Gao; Pengfei Hao; Xin Jin; Yaqing Chang; Jian Song; Donghong Yin; et al. (Marine Biotechnology, 2022)
Polyploid breeding is widely used in aquaculture as an important area of new research. We have previously grown Apostichopus japonicus triploids with a growth advantage. The body length, body weight, and aestivation time of triploid and diploid A. japonicus were measured in this study, and the transcriptome and metabolome were used to examine the growth advantage of triploids A. japonicus . The results showed that the proportion of triploid A. japonicus with a body length of 6–12 cm and 12–18 cm was significantly higher than that of diploid A. japonicus , and triploid A. japonicus had a shorter aestivation time (39 days) than diploid (63 days). We discovered 3296 differentially expressed genes (DEGs); 13 DEGs (for example, cyclin-dependent kinase 2 ) related to growth advantage, immune regulation, and energy storage were screened as potential candidates. According to Gene Ontology (GO) enrichment analysis, DEGs were significantly enriched in the cytoplasm (cellular component), ATP binding process (molecular function), oxidation–reduction process (biological process), and other pathways. According to the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment data, DEGs were significantly enriched in ribosome production and other areas. We discovered 414 significant differential metabolites (SDMs), with 11 important SDMs (for example, nocodazole) linked to a growth advantage. SDMs are significantly enriched in metabolic pathways, as well as other pathways, according to the KEGG enrichment results. According to a combined transcriptome and metabolome analysis, 6 DEGs have regulatory relationships with 11 SDMs, which act on 11 metabolic pathways together. Our results further enrich the biological data of triploid A. japonicus and provide useful resources for genetic improvement of this species.

Metabolomics analysis for skin ulceration syndrome of Apostichopus japonicus based on UPLC/Q-TOF MS - Yang Zhang; Youquan Wang; Xiaoyu Liu; Beichen Ding; Yi Sun; Yaqing Chang; Jun Ding (Journal of Oceanology and Limnology, 2021)